2015
DOI: 10.1021/acs.jpcb.5b04878
|View full text |Cite
|
Sign up to set email alerts
|

Toward Atomistic Resolution Structure of Phosphatidylcholine Headgroup and Glycerol Backbone at Different Ambient Conditions

Abstract: Phospholipids are essential building blocks of biological membranes. Despite a vast amount of very accurate experimental data, the atomistic resolution structures sampled by the glycerol backbone and choline headgroup in phoshatidylcholine bilayers are not known. Atomistic resolution molecular dynamics simulations have the potential to resolve the structures, and to give an arrestingly intuitive interpretation of the experimental data, but only if the simulations reproduce the data within experimental accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
265
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(283 citation statements)
references
References 175 publications
(609 reference statements)
18
265
0
Order By: Relevance
“…The sources of error include an algorithmic implementation (Section 3.1.1), appropriate choice of constant temperature scheme (Section 3. 105 and Pluhackova et al 106 were unable to reproduce previously published results using the GROMOS 54A7 lipid force field with recent versions of the GROMACS simulation package (versions 4.5, 4.6 and 5.1.2) 69,107 , suggesting that this model may not reproduce the experimentally observed phase properties of phosphatidylcholine lipid bilayers modelled under certain hydration and temperature conditions. Specifically, it was found that the area per lipid was lower and the degree of acyl chain order greater than expected.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The sources of error include an algorithmic implementation (Section 3.1.1), appropriate choice of constant temperature scheme (Section 3. 105 and Pluhackova et al 106 were unable to reproduce previously published results using the GROMOS 54A7 lipid force field with recent versions of the GROMACS simulation package (versions 4.5, 4.6 and 5.1.2) 69,107 , suggesting that this model may not reproduce the experimentally observed phase properties of phosphatidylcholine lipid bilayers modelled under certain hydration and temperature conditions. Specifically, it was found that the area per lipid was lower and the degree of acyl chain order greater than expected.…”
Section: Discussionmentioning
confidence: 91%
“…This suggested that either the original parameterisation was incorrect or that results obtained using recent versions of GROMACS differed significantly from those obtained using previous versions of the same code (versions 3.3.3 and 4.0.7). 105,[108][109][110] In MD simulations, the evaluation of long-range pairwise interactions is one of the most resourcedemanding aspects of the algorithm and has been a major focus of efforts to accelerate simulations from the earliest studies. [92][93] Interactions within a system occur over a range of time and length scales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations